2014
DOI: 10.1038/srep06154
|View full text |Cite
|
Sign up to set email alerts
|

Microneedle-mediated immunization of an adenovirus-based malaria vaccine enhances antigen-specific antibody immunity and reduces anti-vector responses compared to the intradermal route

Abstract: Substantial effort has been placed in developing efficacious recombinant attenuated adenovirus-based vaccines. However induction of immunity to the vector is a significant obstacle to its repeated use. Here we demonstrate that skin-based delivery of an adenovirus-based malaria vaccine, HAdV5-PyMSP142, to mice using silicon microneedles induces equivalent or enhanced antibody responses to the encoded antigen, however it results in decreased anti-vector responses, compared to intradermal delivery. Microneedle-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 42 publications
(92 reference statements)
0
34
0
Order By: Relevance
“…Effective cross-talk between innate and adaptive immune responses generates more robust, longer-lasting immune protection [20,21]. We and other investigators have previously reported that skin immunization with metal or dissolving microneedle patches (MNPs) carrying various vaccines (influenza, inactivated poliovirus (IPV), measles, tetanus, HPV, rotavirus, BCG, malaria and RSV) confers immune responses at least non-inferior to conventional immunization as shown by lethal challenge studies, longevity of immune responses and breadth of immunity in a number of small-animal models [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Effective cross-talk between innate and adaptive immune responses generates more robust, longer-lasting immune protection [20,21]. We and other investigators have previously reported that skin immunization with metal or dissolving microneedle patches (MNPs) carrying various vaccines (influenza, inactivated poliovirus (IPV), measles, tetanus, HPV, rotavirus, BCG, malaria and RSV) confers immune responses at least non-inferior to conventional immunization as shown by lethal challenge studies, longevity of immune responses and breadth of immunity in a number of small-animal models [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The applied vaccine can exert a local effect in the skin and a systemic effect following uptake. 1 51,52 in mice. Microenhancer array devices were developed to cause mild abrasion of the SC.…”
Section: Solid Mnsmentioning
confidence: 99%
“…On the day of immunization a 1cm 2 patch was applied to each ear of female 6-8 week old BALB/c mice and pressed, by hand, using a force of approximately 10-20 N per patch, in a vertical direction [15,19,20]. Patches were macroscopically inspected after removal from the ear and no material was found on them; this provided qualitative assurance that microneedles had dissolved from the adhesive backing.…”
Section: Immunisation Studiesmentioning
confidence: 99%
“…Serum antigen-specific IgG responses were assessed as previously described [20] was added for one hour. Plates were washed and incubated with 50µl of TMB for thirty minutes.…”
Section: Antibody Elisamentioning
confidence: 99%
See 1 more Smart Citation